Academic libraries: A soft analysis : a warning and the road ahead - James M. Matarazzo
Abstract Networked access to full-text databases has disrupted both academic and corporate libraries from the research process. The for-profit environment, where libraries are less insulated by organizational prestige and historical tradition, has felt the impact of this more immediately. The changes in corporate libraries, as well as their efforts to remain relevant, can provide insight for academic libraries on how to weather the new realities. Academic libraries will need new strategies to maintain their relationship with students, faculty, and the academy to ensure sustainabili